Experimental and computational investigation of the substituent effects on the reduction of Fe3+ by 1,2-dihydroxybenzenes - Salgado, Pablo (2017)
This study reports on the kinetics of the early steps that mediate the reactions of substituted 1,2-dihydroxybenzenes (1,2-DHB) with Fe3+. The rate constants of the three processes identified by means of the stopped-flow technique are affected by the electron-withdrawing or electron-donating abilities of the substituent. The fastest process is assigned to the formation of a 1:1 complex between Fe3+ and the 1,2-DHB, which is accompanied by proton loss. The second process involves the inner-sphere electron transfer from the ligand to Fe3+ and the slowest step is related to the deprotonation of one of the oxygen atoms bonded to the metal. A reaction mechanism is proposed on the basis of the experimental data and density functional theory (DFT) calculations on mono- and bidentate species with different degrees of protonation.